Digital capture of fingerprints in a disaster victim identification setting: a review and case study - Bryan T. Johnson; John A. J. M. Riemen (Oxford University Press, 2018)
Identification of victims following a mass fatality is conducted by collecting and analysing a series of scientific identifiers and contextual information of each decedent. Recently, there has been a paradigm shift demanding that this complex identification process be accelerated to meet the needs of the surviving families, politicians and even the media. Postmortem fingerprint identification is a fast and efficient means of victim identification, and through the use of new advances in technology, the digital capture of fingerprints in a Disaster Victim Identification (DVI) setting will play a strong role. This paper provides an overview of current technology and explains how this technology can adapt to current DVI procedures. The Malaysian Airlines Flight 17 (MH17) incident is a recent example of a DVI event that utilized new digital fingerprint capture technology and further demonstrates why such technology is warranted in future mass fatality operations.